Implementasi Gerakan Budaya Literasi Sekolah melalui Program MACALAS di kelas 3 MI AL Makmur Mayangrejo - Midya Yuli Amreta Neyha Fadlilatul Ainia; Linda Ayu Sahara; Fitri Hidayati Lestari; Ulfa Nur Fitri Aprilia (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This community service is driven by by the implementation of innovative programs in strengthening literacy and numeracy cultural methods. Therefore, innovation is needed in the application of (MacaLas) literacy to help improve and train students' abilities in reading, writing and conveying ideas. This research uses qualitative methods by collecting data through interviews, observation and document collection. The results of research at MI Al Makmur show that teachers implement various things through (MacaLas) activities at MI Al Makmur Mayangrejo which are carried out regularly with varied learning. method for running the (MacaLas) program. Apart from the variety of methods, the learning media and syntax used also vary. One of the unresolved concerns is the low interest in reading among Indonesian students. Moreover, when books are the only source of information, reading activities have not become a primary need for Indonesia's young generation. Now, even though knowledge can be accessed through various media and e-books are available anytime and anywhere, the level of interest in reading in Indonesia is still relatively low. Reading activities have not yet become a priority in people's lives in the country, School Literacy Movement initiatives have progressed through several levels, beginning with routine reading habits, moving into development, and culminating in integration within learning activities The positive impacts seen are student attitudes that reflect a high literacy ecosystem